Tents and buildings on along Snake River, Nome, Alaska, between 1998 and 1901 - Hester, Wilhelm, 1872-1947 (1998)
Bearing Sea and ships visible. PH Coll 318.1023 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number